Teachers’ Non-Verbal Communication in Teaching English to Young Learners - Maisarah; Trikaloka Handayani Putri; Nailul Fauziyah; Muhammad Saifuddin; Dwi Nurcahyani; Aizun Najih; Bakri (Formosa Journal of Science and Technology, 2023)
The ability to communicate nonverbally is a skill that prospective teachers must master. This current study was to explore the the usage of non-verbal communication by teachers in the highly popular YouTube video titled "How to teach Kids | from a Prague kindergarten, part 2 | English for Children. Based on the non-verbal communication classification by Marcinowicz et al. (2010), which includes Eye contact, Facial expressions, Touch, Interpersonal distance, Gesture, Posture, Tone of voice, and Dress, this study adopts a qualitative approach to analyze the teacher's communication strategies. The results showed that, overall, using nonverbal communication strategies such as eye contact, facial expressions, gestures, tone of voice, and dress by the teachers in the video can enhance the quality of learning and build a good relationship between teachers and students. These strategies can create a fun learning atmosphere, motivate students, and strengthen their understanding of the learning material.